Description of the application method in technical and scientific work on insecticides (Acta Scientiarum. Agronomy, 2016)
Chemical control is a viable and practically indispensable tool in the control and management of cultivated plant pests, but insufficient detail in documenting the methods used for applying phytosanitary products has been reported in the majority of scientific publications dealing with insecticide application. A survey of 200 scientific studies was conducted to examine how much basic information was provided on the application method. The amount of descriptive detail concerning the insecticide application method was found to be below the minimum requirements. In particular, there was insufficient detail concerning the spray droplet spectrum (no information in 173 studies evaluated – 86.5%), operating pressure (38 studies – 19%), solution concentration (52 studies – 26%), distance and position of spray nozzles in relation to the target (114 studies – 57%), temperature (128 studies - 64%), relative humidity (134 studies - 67%) and wind speed (145 studies – 72.5%). All the studies evaluated contained information on the application rate used (L ha-1). To change this situation and reestablish the importance of the application method, we propose a simplified method description for the application of phytosanitary chemicals. Use of the proposed minimum methodological description is practicable for insecticide treatments and will also enable them to be accurately repeated.